The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/cddis.2017.224
|View full text |Cite
|
Sign up to set email alerts
|

Aroclor1254 disrupts the blood–testis barrier by promoting endocytosis and degradation of junction proteins via p38 MAPK pathway

Abstract: The blood–testis barrier (BTB) constituted by coexisting junction apparatus between Sertoli cells (SCs) plays an important role in spermatogenesis, which is a known target of various environmental toxicants. The commercial polychlorinated biphenyls mixture, Aroclor1254, has been shown to impair male reproduction by decreasing sperm count and affecting SC metabolism. This study was designed to investigate the effects of Aroclor1254 on the BTB integrity and elucidate the underlying mechanisms. We found that Aroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Antonetti et al found that changes in occludin phosphorylation state were associated with increased endothelial permeability in response to VEGF . They also demonstrated that phosphorylation at Ser‐490 and ubiquitination were related to occludin decrease in response to VEGF in endothelial cells . In our study, the phosphorylation of occludin at Ser‐490 was verified after VEGF treatment with a phosphosite‐specific antibody.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Antonetti et al found that changes in occludin phosphorylation state were associated with increased endothelial permeability in response to VEGF . They also demonstrated that phosphorylation at Ser‐490 and ubiquitination were related to occludin decrease in response to VEGF in endothelial cells . In our study, the phosphorylation of occludin at Ser‐490 was verified after VEGF treatment with a phosphosite‐specific antibody.…”
Section: Discussionsupporting
confidence: 75%
“…34,35 They also demonstrated that phosphorylation at Ser-490 and ubiquitination were related to occludin decrease in response to VEGF in endothelial cells. [36][37][38][39] In our study, the phosphorylation of occludin at Ser-490 was verified after VEGF treatment with a phosphosite-specific antibody. FLAG-tagged S490DOcc occludin mutants were transfected into HUVECs by plasmid to investigate whether the Ser-490 phosphorylation site is involved in occludin ubiquitination.…”
Section: F I G U R Ementioning
confidence: 52%
“…The integrity of the BTB was evaluated by using EZ-Link Sulfo-NHS-LC-Biotin (Pierce Biotechnology, Rockford, IL, USA) as an indicator as described previously [34-36]. In brief, after TGF-β3 treatment, three or four rats from each group were anesthetized by ketamine HCl (100 mg/kg) via i.p.…”
Section: Methodsmentioning
confidence: 99%
“…To acquire well-purified mature SCs with less germ cells, 20-day-old rats were used for SCs isolation according to a classical method as described [36, 37]. After isolation, the SCs were plated at different densities on Matrigel (BD BioSciences, Franklin Lakes, NJ, USA)-coated culture dishes according to the following detections: 0.5×10 6 /cm 2 on 6-well plates for immunoblot and immunoprecipitation, 1.2×10 6 /cm 2 on Millicell-HA inserts (Millipore, Boston, MA, USA) for SC epithelial permeability barrier assessment, and 0.05×10 6 /cm 2 on cover glass for immunofluorescence analysis.…”
Section: Methodsmentioning
confidence: 99%
“…During this process, regulation of endocytic trafficking of junctional proteins provides a way of rapidly restructuring cell–cell junctions. Failure in any of these steps during endocytosis by Sertoli cells can lead to structural cell junctional defects in the seminiferous epithelium and subsequently an unstable environment for spermatogenesis (Cheng et al, 2011; Jia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%